A new numerical method for stiff differential equations - Boroni, Gustavo Adolfo; Clausse, Alejandro; Lotito, Pablo Andres (Planta Piloto de Ingeniería Química, 2009)
Fil: Boroni, Gustavo Adolfo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tandil; Argentina. Universidad Nacional del Centro de la Provincia de Buenos Aires; Argentina